Environmental Economics an introduction - Field, Barry C.; Field, Martha K. (New York Mcgraw Hill Education, 2021)
Fulltext
Keywords: Environmental economics; Pollution -- Economic aspects; Economic development -- Environmental aspects; Environmental policy